Effects of Litter Materials on Body Weight, Packed Cell Volume and Ectoparasite Dermanyssus gallinae - Setyawati, SJ; Suhermiyati, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
This research aimed to investigate the most suitable litter materials for broiler farming. Ninety six broiler chicken of Cobb Strain (Anwar Sierad) were used. The Experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 6 replications. Each treatment unit consisted of 4 chicken. The treatment applied was litter materials, which consisted of rice husk, rice straw, wood shavings and sawdust. Data obtained were analyzed using analysis of variance and continued with Honestly Significant Difference (HSD). Variables observed were body weight at harvest, packed cell volume (PCV) and number of ectoparasite Dermanyssus gallinae. Results showed that body weight at harvest of broiler kept on wood shavings was significantly (P<0.05) higher than those on the other litter materials. The treatments have no significant effect (P>0.05) on PCV. In addition, wood shavings contained significantly (P<0.05) less mite of Dermanyssus gallinae than the other materials. In conclusion, wood shavings was the best litter material for obtaining broiler body weight at harvest, and contained less ectoparasite microorganism, particularly of Dermanyssus gallinae, than the others. (Animal Production 10(3): 194-197 (2008)Â Key Words: Broiler, litters, harvest, Packed Cell Volume, ectoparasite